#usuttuntas: Representasi kekecewaan terhadap tragedi Kanjuruhan - As'yari, Muhammad (Maliki Interdisciplinary Journal, 2024)
This research examines the disappointing expressions depicted in a hashtag on social media #usuttuntas over the results in Kanjuruhan. The results of this research confirm that the social media opinion movement with the hashtag #usuttuntas has become a strong form of expression for the public to express their disappointment and distrust regarding the handling of the Kanjuruhan Tragedy.